Integrin αvβ3 enhances the suppressive effect of interferon‐γ on hematopoietic stem cells. (3rd July 2017) - Umemoto, Terumasa; Matsuzaki, Yu; Shiratsuchi, Yoshiko; Hashimoto, Michihiro; Yoshimoto, Takayuki; Nakamura‐Ishizu, Ayako; Petrich, Brian; Yamato, Masayuki; Suda, Toshio
Abstract: Hematopoietic homeostasis depends on the maintenance of hematopoietic stem cells (HSCs), which are regulated within a specialized bone marrow (BM) niche. When HSC sense external stimuli, their adhesion status may be critical for determining HSC cell fate. The cell surface molecule, integrin αvβ3, is activated through HSC adhesion to extracellular matrix and niche cells. Integrin β3 signaling maintains HSCs within the niche. Here, we showed the synergistic negative regulation of the pro‐inflammatory cytokine interferon‐γ (IFNγ) and β3 integrin signaling in murine HSC function by a novel definitive phenotyping of HSCs. Integrin αvβ3 suppressed HSC function in the presence of IFNγ and impaired integrin β3 signaling mitigated IFNγ‐dependent negative action on HSCs. During IFNγ stimulation, integrin β3 signaling enhanced STAT1‐mediated gene expression via serine phosphorylation. These findings show that integrin β3 signaling intensifies the suppressive effect of IFNγ on HSCs, which indicates that cell adhesion via integrin αvβ3 within the BM niche acts as a context‐dependent signal modulator to regulate the HSC function under both steady‐state and inflammatory conditions. Synopsis: Besides contributing to maintenance of bone marrow hematopoietic stem cells (HSCs) at homeostasis, integrin β3 signaling potentiates negative regulation of HSCs in the context of the pro‐inflammatory stress cytokine interferon‐γ (IFNγ). Integrin β3 specifies functional LT‐HSCs in IFNγ‐treated stressed mice. Impaired integrin β3 signaling mitigates IFNγ‐dependent suppression of HSCs in chimeric transplantation experiments in vivo . Induction of integrin β3 signaling intensifies IFNγ‐mediated suppression of HSCs. Integrin β3 signaling enhances STAT1‐dependent gene expression via serine 727 phosphorylation during IFNγ stimulation. Abstract : Integrin β3 defines functional hematopoietic stem cells (HSCs) and synergises with inflammatory IFNγ via STAT1 serine phosphorylation to suppress HSC engraftment in vivo .